Performance of chairs from eucalyptus pellita and public acceptation / Nurul Nadhirah Mazlan - Mazlan, Nurul Nadhirah (Faculty of Applied Sciences, 2017)
The purpose of this study is identify the potential of Eucalyptus pellita wood as raw material for wooden furniture industry. The fast growing tree is the most raw material that has been used in furniture industry. The increasing demand to export the wooden furniture from Malaysia was really surprising. Therefore, the tree that has potential and fast growing is seek to supplement the wood that already use in industry furniture. The clear specimen was carried out to find out the properties of the wood. Questionnaire survey (refer Appendix 1) is distributed to the public for identify the acceptance people against the product from the Eucalyptus pellita wood. From the survey appearance factor is in first rank which it most influence by age, followed by gender, status and profession. Chairs was develop to be tested to determine the performance of the chairs towards the Furniture Testing. Result shows that the best quality of chair is Type A with Mortise and Tenon compared to chair Type B with Allen Key Screw. This is because